Effect of Ergonomic Levels on Text Neck Syndrome Among Students: A Correlational Study - Haidar Ahmad Raihan; Farid Rahman (Universitas Muhammadiyah Surakarta, 2023)
Neck pain is a prevalent issue among students, exacerbated by prolonged and non-ergonomic smartphone and laptop use, especially during remote learning. This study aims to examine the influence of ergonomic practices on text neck syndrome. The Neck Disability Index questionnaire assesses text neck syndrome (dependent variable), while the Rapid Upper Limb Assessment (RULA) evaluates ergonomic levels (independent variable). Employing an observational approach at Cililin 1 State Senior High School, West Java, the study involves 292 participants selected purposefully. Ordinal linear regression analysis indicates a significant correlation (p < 0.05) between ergonomic levels and text neck syndrome. The obtained pseudo-R-Square value of 13.1% signifies that ergonomic factors account for 13.1% of the variability. The wald value of 14.240 suggests a heightened risk of text neck syndrome by 14.240 with each unit increase in ergonomic level. In conclusion, this study underscores the substantial contribution of ergonomics (explaining 13.1% of variability) to the occurrence of text neck syndrome, as evidenced by the research outcomes.